2015
DOI: 10.1007/s13201-015-0368-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of reference evapotranspiration using multivariate fractional polynomial, Bayesian regression, and robust regression models in three arid environments

Abstract: The proper evaluation of evapotranspiration is essential in food security investigation, farm management, pollution detection, irrigation scheduling, nutrient flows, carbon balance as well as hydrologic modeling, especially in arid environments. To achieve sustainable development and to ensure water supply, especially in arid environments, irrigation experts need tools to estimate reference evapotranspiration on a large scale. In this study, the monthly reference evapotranspiration was estimated by three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 51 publications
(16 reference statements)
0
39
1
1
Order By: Relevance
“…Gong et al (2003) also reported that application of Si improved water economy and increased the growth of plants under water stress condition. Increase in evapotranspiration as result of thermal stress (Valipour 2015a;Khoshravesh et al 2015) could lead to a reduction in the rate of photosynthesis (Almeselmani and Deshmukh 2012). Late planted wheat decreased the photosynthetic rate that was associated with higher evapotranspiration (Valipour 2015b) and stomatal conductance (Takahashi and Nakaseko 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al (2003) also reported that application of Si improved water economy and increased the growth of plants under water stress condition. Increase in evapotranspiration as result of thermal stress (Valipour 2015a;Khoshravesh et al 2015) could lead to a reduction in the rate of photosynthesis (Almeselmani and Deshmukh 2012). Late planted wheat decreased the photosynthetic rate that was associated with higher evapotranspiration (Valipour 2015b) and stomatal conductance (Takahashi and Nakaseko 1992).…”
Section: Discussionmentioning
confidence: 99%
“…2 The accuracy of the time series models increased with increasing amounts of observation data of arid and humid climates. 3 Time series models are appropriate tools for forecasting monthly rainfall forecasting in semi-arid climates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ARIMA models are non-static and cannot be used to reconstruct the missing data. However, these models are very useful for forecasting changes in hydrological processes considering agricultural water management, evapotranspiration, and water crisis issues [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Models of time series analysis (Box-Jenkins models) in various fields of hydrology and rainfall forecasting in irrigation schedules are widely applied, some of which will be described in what follows.…”
Section: Introductionmentioning
confidence: 99%
“…If increased temperature is above the threshold of crops, it will lead to the death of crops (Thornton et al, 2009). In addition, evapotranspiration (ET) is one of the major components of the hydrologic cycle and it is supreme important for many investigations such as irrigation scheduling, crop yield simulation and farm management, particularly in arid environments (Khoshravesh et al, 2015;Valipour, 2014a, b). Thus, higher temperature and erratic rainfall will be expected to have a negative influence on the suitability of these three crops (teff, maize, wheat) (Figures 4, 5, and 6) through decreasing their growth and duration (Gregory et al, 2005).…”
Section: Discussionmentioning
confidence: 99%